2009
DOI: 10.1080/09638280802572965
|View full text |Cite
|
Sign up to set email alerts
|

What factors predict full or partial return to work among sickness absentees with spinal pain participating in rehabilitation?

Abstract: Even patients with long previous sick leave can increase working time after a multidisciplinary rehabilitation programme, especially if they are younger, have lower levels of activity limitations and pain and better social functioning. To include information on part-time work is useful when evaluating work ability following rehabilitation programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
1
27
0
2
Order By: Relevance
“…This study by Puolakka et al (2008) indicated that motivation to work was associated with fewer days off work, but not with permanent work disability. Two studies with a low risk of bias did not find any association between motivation and work participation (Elfving et al 2009; Wan Kasim et al 2014). Seven qualitative studies addressed the possible positive influence of motivation, which suggests that employees with health problems who are motivated will have higher levels of work participation (Åhrberg et al 2010; De Vries et al 2011; Dekkers-Sánchez et al 2010; Dunn et al 2010; Hartke et al 2011; Van Velzen et al 2011; Wilbanks and Ivankova 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This study by Puolakka et al (2008) indicated that motivation to work was associated with fewer days off work, but not with permanent work disability. Two studies with a low risk of bias did not find any association between motivation and work participation (Elfving et al 2009; Wan Kasim et al 2014). Seven qualitative studies addressed the possible positive influence of motivation, which suggests that employees with health problems who are motivated will have higher levels of work participation (Åhrberg et al 2010; De Vries et al 2011; Dekkers-Sánchez et al 2010; Dunn et al 2010; Hartke et al 2011; Van Velzen et al 2011; Wilbanks and Ivankova 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Despite relatively little formal validation of the TSK in people with neck pain, it has been used as a prognostic indicator following acute injury 22,23 and as a modifier of treatment effectiveness in that population. 24 Whether in neck pain or other conditions, the score on the TSK has almost universally been evaluated using statistical approaches that should be reserved for linear measurement. The degree to which such practices actually affect results is debatable (see Knapp 25 for a review of these controversies).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of socioeconomic status and LBP (including income, education and occupation) have also had mixed results. There are frequent reports that lower income, less education and employment in manual occupations is associated with increased pain and disability [60,61,[66][67][68][69], but other studies report no associations [64,65,68,70]. There is very little research examining the association between race/ethnicity and LBP.…”
Section: Social Disadvantagementioning
confidence: 91%
“…Longitudinal studies of LBP prognosis typically include demographic assessments of age, gender, income, education and race/ethnicity, and these variables might be considered as a general metric of social standing. The majority of LBP studies report older age and female gender as risk factors for poorer LBP outcomes [59][60][61][62][63], but some studies report no such effects [64,65]. Studies of socioeconomic status and LBP (including income, education and occupation) have also had mixed results.…”
Section: Social Disadvantagementioning
confidence: 93%